SCOPE OF PREVENTIVE SERVICES PROVIDED BY CHOSEN DOCTORS IN PRIMARY HEALTH CARE, IN THE REPUBLIC OF SERBIA, IN THE PERIOD BETWEEN 2013 AND 2017 - Milosevic, Mirjana; Topalovic, Marina; Jovic-Vranes, Aleksandra (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: In the Republic of Serbia, the capitation formula was introduced in 2012, as a payment for performance model for chosen medical doctors based on the number of patients, number of visits, financial value of prescribed prescriptions, as well as on the basis of the number of preventive health services provided in public primary health care facilities. Aim: The aim of this paper is to analyze the scope of preventive health services provided, which is used to evaluate the performance and to pay selected doctors according to the capitation formula, in primary health care institutions, in the Republic of Serbia, in the period between 2013 and 2017.Methods: The available data of the Institute of Public Health of Serbia ‘Dr Milan Jovanović – Batut’ (IPHS ‘Batut’), in terms of the coverage of certain populations with health services, were analyzed, namely twenty-three different indicators, i.e., preventive services provided by chosen medical doctors in the area of health services for adults, children, and women's healthcare, in 166 primary health care institutions to which the payment model based on the capitation formula is applied (158 primary healthcare centers, three institutes for the health care of university students, and five institutes for the health care of workers). The trend of coverage of the above-mentioned services, in the period between 2013 and 2017 was examined, as well as the increase in the volume of preventive services, with fixed-base and chain indices.Results: Three out of twenty-three different health services showed a declining trend, namely the coverage of infants with ultrasound examinations for early detection of hip dysplasia, coverage of schoolchildren with preventive examinations at the ages of 8, 10, 12, and 14 years, as well as coverage of the adult population (older than 35 years) with preventive services. All other services had a stable trend in terms of coverage of target populations in the period from 2013 to 2017. Conclusion: Although most of the observed preventive health services had a stable trend of population coverage, their coverage was far below the recommended level, in the observed period.
Keywords: primary health care; payment for performance; chosen doctor; preventive health services; capitation formula